2019
DOI: 10.1002/met.1854
|View full text |Cite
|
Sign up to set email alerts
|

Observed and model‐simulated thermodynamic processes associated with urban heavy rainfall events over Bangalore, India

Abstract: A total of 32 rainfall events spanning the period from 2012 to 2014 over the urban Indian city of Bangalore were simulated using the Weather Research and Forecast (WRF) model. Model simulations were carried out with a four‐nested domain initialized with Global Forecast System (GFS) data and the forecast was generated on an hourly basis. The forecasted rainfall at hobli level (Bangalore has 34 hobli divisions with an area of each hobli of the order of about 10 km2) was evaluated in terms of its intensity and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…The stability indices K, LI, TT, SWEAT, CAPE and CIN, and PW were calculated from the vertical profiles of temperature, pressure, and relative humidity collected by the radiosondes (Dong et al, 2018;do Carmo et al, 2019;Guerova et al, 2019;Ajilesh et al, 2020). In the following formulas, the notation used is: T = environmental temperature, TD = dew point temperature, TP = temperature of the parcel, θ = virtual temperature of the environment, θP = virtual temperature of the parcel, f = wind speed, w = direction of the wind, and g = acceleration of gravity.…”
Section: Methodsmentioning
confidence: 99%
“…The stability indices K, LI, TT, SWEAT, CAPE and CIN, and PW were calculated from the vertical profiles of temperature, pressure, and relative humidity collected by the radiosondes (Dong et al, 2018;do Carmo et al, 2019;Guerova et al, 2019;Ajilesh et al, 2020). In the following formulas, the notation used is: T = environmental temperature, TD = dew point temperature, TP = temperature of the parcel, θ = virtual temperature of the environment, θP = virtual temperature of the parcel, f = wind speed, w = direction of the wind, and g = acceleration of gravity.…”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic properties are mainly associated with temperature profile and moisture content determining the convection process (Pall et al 2007;Lepore et al 2015). Thermodynamic indices are important to understand the atmospheric instability, which ultimately triggers the rainfall (Ajilesh et al 2020). Manandhar et al (2019b) stated that for temperate and subtropical regions, an apparent change in PWV values is observed certain hours before the rain.…”
Section: Relationship Between Pwv and Rainfallmentioning
confidence: 99%
“…In Nigeria, it has been found that the seasonal variability patterns of the atmospheric instability parameters and rainfall are similar (Matthew et al 2021). Also, in the tropics, much of the urban heavy rainfall events are enhanced by the organized convection in the lower troposphere, and the atmospheric thermodynamic indices (atmospheric instability indices) which depend on temperature and/or dew point temperature at specific geopotential height levels are important in the determination of such organized convections (Ajilesh et al 2020).…”
Section: Introductionmentioning
confidence: 99%